2009
DOI: 10.1016/j.carbon.2009.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of PEEK/carbon nanotube composites

Abstract: New poly(ether ether ketone) (PEEK) based composites have been fabricated by the incorporation of single-walled carbon nanotubes (SWCNTs) using melt processing. Their structure, morphology, thermal and mechanical properties have been investigated. Scanning electron microscopy observations demonstrated a more uniform distribution of the CNTs for samples prepared following a processing route based on polymer ball milling and CNT dispersion in ethanol media. Thermogravimetric analysis indicated a remarkable impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
133
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 184 publications
(154 citation statements)
references
References 47 publications
17
133
2
2
Order By: Relevance
“…2b corresponds to a region between fiber tows of the laminate incorporating 1.0 wt% non-wrapped arc-SWCNTs, showing the existence of small CNT agglomerates (see the circle marked on the image). As can be visualized in the inset, the aggregates form a highly entangled interconnected structure, with SWCNT bundle diameters in the range 30-60 nm, values similar to those found previously for PEEK/arc-SWCNT composites [25]. These SWCNT aggregates (bigger than 2 lm) envelop the fiber tows but do not penetrate into them.…”
Section: Morphological Observationssupporting
confidence: 80%
See 2 more Smart Citations
“…2b corresponds to a region between fiber tows of the laminate incorporating 1.0 wt% non-wrapped arc-SWCNTs, showing the existence of small CNT agglomerates (see the circle marked on the image). As can be visualized in the inset, the aggregates form a highly entangled interconnected structure, with SWCNT bundle diameters in the range 30-60 nm, values similar to those found previously for PEEK/arc-SWCNT composites [25]. These SWCNT aggregates (bigger than 2 lm) envelop the fiber tows but do not penetrate into them.…”
Section: Morphological Observationssupporting
confidence: 80%
“…Arc and laser-grown SWCNTs were synthesized following the procedures reported in our previous works [25,26]. The compatibilizing agent poly(1-4-phenylene ether-ether sulfone), PEES (M w $ 38,000 g/ mol, T g = 192°C, d 25°C = 1.38 g/cm 3 ), was provided by Sigma-Aldrich in pellet form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthy to notice that the average bundle diameters of the SWCNTs dispersed in PSF and PEES (Table 1) are smaller than the values obtained from SEM images of the non-wrapped SWCNTs [17]. This indicates that the addition of the polysulfones leads to a significant CNT disentanglement and debundling, and thereby confirms their efficiency as compatibilizing agents.…”
Section: Carbon Nanotube Dispersion In the Compositesmentioning
confidence: 76%
“…Over the last decades many studies have been reported on the structural [11], mechanical [12] and thermal [13] characterization of this linear aromatic polymer, albeit only a few papers deal with such composites made of a PEEK matrix; the most relevant are those published by Shaffer et al [14], working with vapor-grown carbon nanofiber/PEEK composites, Deng et al [15], dealing with multi-walled carbon nanotube (MWCNT)/PEEK nanocomposites, and Song et al [16], who prepared sandwich like SWCNT paper/PEEK composites. Recently, our group reported the synthesis and characterization of PEEK/SWCNT composites [17]. We have developed strategies to efficiently incorporate the nanotubes in the PEEK matrix.…”
Section: Introductionmentioning
confidence: 99%